Effect of Cognitive Behavioral Therapy on tobacco usage and dependency among adult male tobacco users in Palam area of Delhi - Kumar, Rajindra; Goel, Manish Kumar; Talukdar, Tanmaya (Indian Journal of Community Health, 2024)
Background: Tobacco use is a recognized risk factor for many chronic diseases such as chronic obstructive pulmonary disease (COPD), hypertension, cardiovascular disease, atherosclerosis, diabetes, cancer and microbial infections (respiratory tract infections, bacterial meningitis), etc. Material and Methods: A community-based "One group" interventional study was conducted to see the effect of cognitive behavioural therapy in reducing tobacco usage and its dependency among all the adult males population aged 18 years and above residing in Palam area of Delhi. Data was collected using a semi-structured, self-designed interview schedule to collect information from study subjects. Fagerstrom and Modified Fagerstrom questionnaire was used to assess the subject’s nicotine dependence status. Result: The total population study was 274 out of which 105 were tobacco users. Out of 105,2 did not give consent for cognitive behaviour therapy.A total of 103 study subjects were given cognitive behavioral therapy and then followed at 2 weeks, 4 weeks, 3 months, and 6 months respectively, and analyzed for quitting at each follow-up. Study subjects who had quitted tobacco was 11 i.e. 10.6%. Change in Nicotine dependency was statistically significant. Conclusion: Cognitive behaviour therapy is found to be a very effective tool in reducing tobacco usage as well as nicotine dependency.